Bioprospecting of Bacillus species from East Kalimantan, Indonesia for developing sustainable mosquito larvicides - NOVA HARIANI; BUDIMAN BUDIMAN; FATMAWATI PATANG; ERVINDA YULIATIN (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Hariani N, Budiman, Patang F, Yuliatin E. 2025. Bioprospecting of Bacillus species from East Kalimantan, Indonesia for developing sustainable mosquito larvicides. Biodiversitas 26: 1360-1366. Climate change, unplanned urbanization, environmental pollution, and the development of insecticide-resistant mosquito populations have increased Vector-Borne Disease (VBD) incidents in tropical and subtropical countries. They require an innovative and sustainable action strategy. As the endemic area of VBDs, East Kalimantan stores unexplored biocontrol agents such as Bacillus species. Therefore, this study tested the toxicity of nine single and three mixed isolates of Bacillus from East Kalimantan against mosquito larvae of both Aedes aegypti and non-Ae. aegypti species; and identified the selected Bacillus isolates using a 16S rDNA sequence approach. Five single isolates of Bacillus from East Kalimantan (BP1, BP2, BP3, BF2, and BF3) and their consortia (BPM, BFM, and BFP) decreased the larvae number over time. They demonstrated high effectiveness in reducing Ae. aegypti and non-Ae. aegypti larvae population with more than 50% mortality at 48 hours of exposure. However, utilizing a single isolate of Bacillus as a biocontrol agent against mosquitoes was preferred over using mixed isolates for efficiency in larvacide production, offering a sustainable alternative to chemical insecticides. Moreover, Bacillus-BP3 and Bacillus-BF2 isolates from East Kalimantan, identified as Bacillus subtilis, were strong and safe candidates for developing sustainable larvicides to control mosquito populations with larvae mortality percentage up to 100% in 24 hours, mainly Ae. aegypti. Other isolates were identified as Bacillus cereus (BP1) and Bacillus tropicus (BP2), which also showed high and consistent larvacide activity from the beginning of the exposure.